LEGAL CERTAINTY OF ONLINE MOTORCYCLE TAXI DRIVERS IN THE PERSPECTIVE OF COMPARISON WITH MALAYSIA - Wadrianto, Glori Kyrious; Winanti, Atik (LPPM Univ. Ibn Khaldun Bogor, 2025)
The emergence of the gig economy, driven by advancements in technology, carries notable legal consequences, particularly in Indonesia. This research highlights the lack of legal clarity concerning online transportation (ojek online) drivers, who represent a key segment of gig workers. These drivers are designated as